Prototype of Control and Monitor System with Fuzzy Logic Method for Smart Greenhouse - Didik Kurniawan; Arita Witanti (Indonesian Journal of Information Systems, 2021)
To increase plant productivity, greenhouse buildings are needed that can protect plants from external factors and integrated with smart systems that can be monitored anytime and anywhere, and can provide optimal plant needs automatically. In this research, a system was built that can monitor greenhouse conditions in real time anywhere through Blynk application with IoT concept, as well as a system that can control output automatically with fuzzy logic method. The focus of control on this research is the duration of watering with Mini Water Pump and light intensity setting with LED Strip. This system is also equipped with FAN that can be active when the temperature is 31°C or more. Parameters used in this system are DHT22 sensor (air temperature and humidity), Soil Moisture sensor, Water Level sensor ,LDR sensor (light intensity) and RTC DS3231 (Real Time Clock), which is controlled with Arduino Mega 2560 microcontroller. In the test results obtained accuracy on fuzzy logic water pump by 93.1% and accuracy on fuzzy logic LED Strip by 99.6%. In the test results of the existing parameters, the results get a fairly optimal reading.